Morphological and molecular characterization within 26 strains of the genus Cylindrospermum (Nostocaceae, Cyanobacteria), with descriptions of three new species - Johansen, Jeffrey R; Bohunická, Markéta; Lukešová, Alena; Hrčková, Kristýna; Vaccarino, Melissa A; Chesarino, Nicholas M (Journal of phycology, 2014)
Twenty-six strains morphologically identified as Cylindrospermum as well as the closely related taxon Cronbergia siamensis were examined microscopically as well as phylogenetically using sequence data for the 16S rRNA gene and the 16S-23S internal transcribed spacer (ITS) region. Phylogenetic analysis of the 16S rRNA revealed three distinct clades. The clade we designate as Cylindrospermum sensu stricto contained all five of the foundational species, C. maius, C. stagnale, C. licheniforme, C. muscicola, and C. catenatum. In addition to these taxa, three species new to science in this clade were described: C. badium, C. moravicum, and C. pellucidum. Our evidence indicated that Cronbergia is a later synonym of Cylindrospermum. The phylogenetic position of Cylindrospermum within the Nostocaceae was not clearly resolved in our analyses. Cylindrospermum is unusual among cyanobacterial genera in that the morphological diversity appears to be more evident than sequence divergence. Taxa were clearly separable using morphology, but had very high percent similarity among ribosomal sequences. Given the high diversity we noted in this study, we conclude that there is likely much more diversity remaining to be described in this genus.
Keywords: 16S-23S ITS; Cylindrospermum; 16S rRNA gene; polyphasic approach; Nostocaceae